Maskinen i verktøykassa (AmS-Varia, 2020)
We need to address the way shifting methods in archaeology affect the knowledge of the past. The current use of rural areas for cultivation or pasture, dictates our choice of survey- and excavation methods in development-led archaeology. While the focus is placed on visibility in areas currently used as pastures, there is a tendency not to discuss what might have been removed in cultivated areas. If we let the understanding of prehistoric land use be dictated by modern land use, we risk creating two sets of knowledge of the past which appear mutually exclusive. It is crucial that material from both cultivated fields and pastures are treated as differently preserved fragments of the same archaeological phenomena. The excavation at Myklebust, Sola municipality provides an example of the challenges stemming from the application of different methodologies and interpretations due to modern land use. Regarding the long-term use of sites such as Myklebust, modern historicism provides a view of temporality which runs to the heart of the discipline. The concentrated, multi-phase, chaotic nature of archaeological remains at this site is considered key to the importance of these sites, for both past and present practices. It can take time to revise or update long-held views of the past, and of what are considered the most suitable ways of deepening our knowledge of that past. If excavation and fieldwork are to play a central part in research development, it must begin with our willingness to broaden our perspectives in terms of field practices.